North American Women in Iceland: Travel, Travel Writing, and Domestic Feminism, 1866-1939 - Melton, Zachary (Scandinavian-Canadian Studies / Études scandinaves au Canada, 2024)
In the late nineteenth and early twentieth centuries, dozens of travel narratives about Iceland appeared in the United States. The majority of these were written by and for men and women of the wealthier, upper class, as those were the only Americans who could afford to make the long journey to Iceland. However, as the costs of steamship travel became more affordable, a more economically diverse collection of American tourists began visiting Iceland. In many cases, middle-class American women would journey to Iceland and then share their experiences by giving lectures and talks in social clubs, writing articles in more female-focused periodicals like Ladies’ Home Companion, or to giving interviews in their hometown newspapers. In this paper, I will explore the “feminine” space of the social club and the role it played in the perception of Iceland among middle class American women.